2021
DOI: 10.3390/jcm10122685
|View full text |Cite
|
Sign up to set email alerts
|

Survival Associations between Patient Age and Treatment Modality in Olfactory Neuroblastoma: A Retrospective Population-Based Study

Abstract: Olfactory neuroblastoma (ONB) is a rare neuroepithelial-derived malignancy that usually presents in the nasal cavity. The rarity of ONB has led to conflicting reports regarding associations of patient age and ONB survival and outcome. Moreover, long-term outcomes of chemotherapy and other treatment modalities are speculated. Here, we aimed to compare survival outcomes across age groups through time and determine associations between treatment modality and survival. In this retrospective population-based study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…This difference was significant in multivariate analysis as well. These findings are in concurrence with the findings of two large population database studies which brought out the detrimental effects of chemotherapy [ 8 , 30 ]. The poor outcomes for patients who received chemotherapy could be a reflection of the fact that the majority of the patients who were given chemotherapy had either Kadish C or D disease and most had unresectable disease or had difficult RT planning.…”
Section: Discussionsupporting
confidence: 89%
“…This difference was significant in multivariate analysis as well. These findings are in concurrence with the findings of two large population database studies which brought out the detrimental effects of chemotherapy [ 8 , 30 ]. The poor outcomes for patients who received chemotherapy could be a reflection of the fact that the majority of the patients who were given chemotherapy had either Kadish C or D disease and most had unresectable disease or had difficult RT planning.…”
Section: Discussionsupporting
confidence: 89%
“…44 One possible explanation for this result was that a great majority of patients with ONB who were treated with CT in the SEER database experienced distant metastases or underwent multimodality treatment, which might lead to an inferior CSS. 44 To date, there are few studies exploring the role of CT in patients with LA ONB. LA ONB exhibited a high propensity of invasion to adjacent organs and tissues; therefore, some previous studies have demonstrated that LT alone, including RT and/or SG, might not be sufficient to manage LA ONB.…”
Section: Discussionmentioning
confidence: 99%
“…A recent SEER database analysis of 882 patients with ONB showed that CT was associated with decreased cancer‐specific survival (CSS) 44 . One possible explanation for this result was that a great majority of patients with ONB who were treated with CT in the SEER database experienced distant metastases or underwent multimodality treatment, which might lead to an inferior CSS 44 . To date, there are few studies exploring the role of CT in patients with LA ONB.…”
Section: Discussionmentioning
confidence: 99%
“…The grade of ONB is classified according to Hyams and substantially affects prognosis [78][79][80]. Moreover, prognosis of ONB is negatively impacted by advanced age, male gender, locally advanced stage, nodal involvement, and positive margins [4,[81][82][83][84][85][86]. Classification of local extension is more controversial in contrast to the previously mentioned cancers.…”
Section: Olfactory Neuroblastomamentioning
confidence: 99%